2019
DOI: 10.1038/s41379-019-0248-2
|View full text |Cite
|
Sign up to set email alerts
|

Stage IV lung carcinoids: spectrum and evolution of proliferation rate, focusing on variants with elevated proliferation indices

Abstract: The spectrum and evolution of proliferation rates in stage IV lung carcinoids is poorly defined. In particular, there are limited data on the prevalence and characteristics of tumors exceeding the standard upper proliferative criteria – as defined largely based on early-stage carcinoids – in metastatic setting.Sixty-six patients with stage IV lung carcinoids were identified, and all evaluable samples (n=132; mean 2 samples per patient) were analyzed for mitotic counts and Ki-67 rate. Clinicopathologic and geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 57 publications
3
62
0
Order By: Relevance
“…A molecular study by next-generation sequencing (NGS) also found a "carcinoid-like" subgroup among highly proliferative LNET [7]. This entity was also observed in a recent large study of stage IV carcinoids, accounting for 27% of the samples [8]. There is still no consensus concerning the name of this entity and the terms "high-grade lung carcinoids," "grade 3 atypical carcinoids," "high-grade lung NET," "lung NET G3," "lung well-differentiated neuroendocrine neoplasms with a Ki-67 > 20%," "lung carcinoid with a Ki-67 > 20%," or "high-grade NEC of the lung with carcinoid morphology" have been discussed [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…A molecular study by next-generation sequencing (NGS) also found a "carcinoid-like" subgroup among highly proliferative LNET [7]. This entity was also observed in a recent large study of stage IV carcinoids, accounting for 27% of the samples [8]. There is still no consensus concerning the name of this entity and the terms "high-grade lung carcinoids," "grade 3 atypical carcinoids," "high-grade lung NET," "lung NET G3," "lung well-differentiated neuroendocrine neoplasms with a Ki-67 > 20%," "lung carcinoid with a Ki-67 > 20%," or "high-grade NEC of the lung with carcinoid morphology" have been discussed [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 54%
“…Lung neuroendocrine neoplasms with morphologic features of carcinoid tumours but of high grade have recently been reported. They are rare tumours, the largest recent series describing the pathological aspect of 12 and 28 cases [6,8]. Their definition does not reach consensus yet and they are not included in the official WHO classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach in this paper is similar to other large SEER studies [3 24] but can definitely alter the reported results. The GI NEN literature is moving to a more uniform grading of neoplasms and there is a trend to use proliferation markers to predict outcomes in lung NENs as well [25,26] but this is far from a settled argument. Another issue is that classification of pancreatic NENs (and most recently other GI NENs) has changed to include a category of "well differentiated, high grade" with a prognosis intermediate between G2 and G3.…”
Section: Discussionmentioning
confidence: 99%
“…1). This subgroup might comprise high-grade NET, which has been recently described in several studies although not recognized in current WHO classification (19, 20, 21). However, in those series, the tumors had a carcinoid morphology and absence of TP53 and RB1 mutations.…”
Section: Discussionmentioning
confidence: 96%